Caregiving experiences of South African mothers of adults with intellectual disability who display aggression: clinical case studies - Coetzee, Jacobus (Ockert) (Department of Psychiatry and Mental Health, 2017)
Background: Adults who have an intellectual disability (ID) often continue to live with their parents long after their siblings have left home. While an increasing body of research has described positive parental experiences, research has also found that parents of adults who have ID and behavioural difficulties are more vulnerable to develop parental stress and depression. Aggression is one of the most difficult forms of problem behaviours to manage and could have a negative impact on the parent-child relationship, the child's social inclusivity and the psychological well-being of parents. Method: A case-based psychotherapy design was used to explore maternal experiences among mothers of adults with ID and aggression who access a specialised mental health service in Cape Town. Psychotherapy was used with six participants to attempt to reduce parental stress and other negative psychological states. In an area of research that has received scant attention in South Africa, the study extensively describes the psychotherapy process and the role of contextual factors in the lives of the participating mothers. The study used a mixed methods design which included psychometric measurements that were conducted at various intervals of intervention. Thematic analysis was used in all the case studies and interviews were scheduled before and after completing psychotherapy. External credibility was enhanced through the use of different qualitative strategies that included peer supervision and reflexivity. Findings: Besides elevated parental stress, the majority of participants presented with symptoms of depression and other mental health problems that varied according to their individual profiles. Although parental stress showed a discernible relationship with the child's behavioural difficulties, other significant life stressors contributed to maternal stress and depressive symptoms. Psychotherapy produced only modest improvement of parental stress among some of the participants. However, therapeutic input appeared to be more effective in reducing depressive symptoms among the majority of mothers. Critical reflection and discussion are centred on the clinical implications and meaning of findings on a psychological level.